Health effects of mixed metal exposure on accelerating aging among the elderly population - Chuanli Yang; Jijun Zhang; Haohan Liu; Qin Hong; Yunhe Fan; Jie An; Haijia Zhang; Xiaobing Shen; Xiushan Dong (Ecotoxicology and Environmental Safety)
Background: Human exposure to heavy metals occurs through multiple pathways in daily life. However, the effects of mixed heavy metal exposure on accelerated aging in the elderly U.S. population remains unclear. This study aims to investigate the association between heavy metal concentrations in blood and urine and the onset of accelerated aging. Methods: A total of 2530 individuals were included in the blood metals analysis and 716 individuals in the urine metals analysis in this study. GrimAge acceleration (AgeAccelGrim) was calculated as the residuals from regressing DNA methylation GrimAge on chronological age. Weighted multivariable logistic regression models were applied to analyze the relationship between metal exposure with AgeAccelGrim. Bayesian kernel machine regression (BKMR) was performed to estimate the effects of individual metals or metals mixtures and AgeAccelGrim. Results: We found that blood cadmium (Cd) concentration was positively associated with an increased risk of AgeAccelGrim in both females and males, with odds ratios (OR) of 5.73 (95 % confidence interval (95 % CI): 1.88–17.41, P trend = 0.008) and 14.25 (95 % CI: 4.88–41.62, P trend < 0.001), respectively. Moreover, these associations were more pronounced for urinary Cd compared to blood Cd. Blood lead (Pb) was also associated with a 3.52-fold (95 % CI: 1.21–10.24, P trend = 0.007) increase in AgeAccelGrim risk among males. BKMR confirmed the aforementioned findings, identifying Cd as the most significant contributor to accelerated aging. Conclusions: Exposure to heavy metals, either individually or in mixture, was positively associated with accelerated biological aging. These associations were more pronounced in males.